2008
DOI: 10.1155/2008/125678
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis of Thermodynamic Effect of Cavitation in Cryogenic Inducer Using Singularity Method

Abstract: Vapor production in cavitation extracts the latent heat of evaporation from the surrounding liquid, which decreases the local temperature, and hence the local vapor pressure in the vicinity of cavity. This is called thermodynamic/thermal effect of cavitation and leads to the good suction performance of cryogenic turbopumps. We have already established the simple analysis of partially cavitating flow with the thermodynamic effect, where the latent heat extraction and the heat transfer between the cavity and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…They suggested the nondimensional thermal parameter, R Ã , in a different way. They found that: 1) as R Ã increases, the onset cavitation number of cavitation instabilities moved toward lower cavitation number [19] and 2) temperature effects were more significant at higher temperatures, and temperature effects became larger as the cavitation bubble becomes longer due to the need of larger latent heat [20]. Tokumasu et al [21] performed a numerical simulation of a two-dimensional hydrofoil and found that the size of cavitation was smaller and temperature drop was smaller at a higher temperature liquid oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested the nondimensional thermal parameter, R Ã , in a different way. They found that: 1) as R Ã increases, the onset cavitation number of cavitation instabilities moved toward lower cavitation number [19] and 2) temperature effects were more significant at higher temperatures, and temperature effects became larger as the cavitation bubble becomes longer due to the need of larger latent heat [20]. Tokumasu et al [21] performed a numerical simulation of a two-dimensional hydrofoil and found that the size of cavitation was smaller and temperature drop was smaller at a higher temperature liquid oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…is probably due to the interaction between the cavity and the flow around the leading edge of the adjacent blade. This situation was also commented in [23].…”
Section: Near-shroud Cutmentioning
confidence: 52%
“…In actual rocket engines using liquid oxygen, Σ * ranges from 1.5 to 30 depending on the size and rotational speed of the inducer. Watanabe et al (2007Watanabe et al ( , 2008 independently derived the non-dimensional thermal parameter Σ * in their analysis of an inducer cascade and found that increasing Σ * suppressed the onset of cavitation instabilities. Kikuta et al (2009) investigated the rotational speed effects using Σ * in liquid nitrogen.…”
Section: σ=mentioning
confidence: 99%